Nano-porous silica-aerogel-incorporated composite materials for thermal-energy-efficient pitched roof in the tropical region - Ismail, F.I. (MDPI AG, 2021)
Silica aerogel possesses an ultra-low thermal conductivity by virtue of its nano-structure. Owing to the fragility of monolithic aerogel, the development and production of aerogel-based insulation materials involve the incorporation of granular aerogel with other materials to form composite materials. In the present study, the application of silica-aerogel-incorporated composite cement paste as render on the roof-top surface is coupled with the installation of a novel silica-aerogel-incorporated composite insulation board below the roof tiles. Control and silica-aerogel-incorporated samples of the composite cement paste and insulation were prepared. Thermal conductivity and strength tests were performed on the samples. A simulation study was performed on a Building Information Model subjected to a tropical climate to project the resultant impact of the cement render coupled with the insulation board on the thermal-energy-efficiency of the roof. For optimization of thermal and strength performances, silica aerogel contents of 4 wt. and 3 wt. were selected for the cement render and insulation board, respectively. The projected annual cooling load and energy savings revealed that the application of a 20-mm cement render, coupled with the installation of a 100-mm thick insulation board, is recommended as the optimum roof configuration. Â© 2021 by the authors. Licensee MDPI, Basel, Switzerland.